Vocal Cord Paralysis and Respiratory Muscle Weakness: An Unusual Presentation of Chronic Polyneuropathy. Issue 2 (3rd April 1998) - Chau, LKL; Webb, KA; Jackson, AC; O'Donnell, DE
Abstract : A case of chronic polyneuropathy that manifested with an unusual combination of vocal cord paralysis and respiratory muscle weakness is reported. In addition, results of an exercise test carried out to assess the severity and mechanisms of exertional breathlessness in this unique condition with combined obstructive and restrictive disorders are described.